Rehabilitation of damaged reefs: Outcome of the use of recently broken coral fragments and healed coral fragments of pocilloporid corals on rocky boulders. (21st October 2017) - Nava, Héctor; Figueroa‐Camacho, Antonieta G.
Abstract: The use of two types of coral transplants on rock boulders was evaluated as a low‐cost alternative for rehabilitation of live coral coverage in localities whose reef structure has been reduced considerably. Transplant success between recently broken coral fragments (BCF) and healed coral fragments (HCF) was compared assuming that initial fragmentation accelerates the attachment of corals by regeneration stimulation. Two sets of both types of transplants were started during the dry and rainy seasons to contrast the effect of environmental stability on transplant survival, vertical growth and horizontal growth over 12 months. The technique provided adequate conditions for coral development, as transplants responded satisfactorily. BCF showed higher success than HCF in attaching to the substrate (up to 98 ± 4% versus 86.4 ± 18.9% after 9 months) during both seasons and also showed a greater increase in height (209.63 ± 43.65% versus 124 ± 15.83%) and diameter (107.26 ± 25.75% versus 99.98 ± 19.74%) during the rainy season. Boat anchorage caused mortality in transplants started during the dry season (less than 10% for BCF versus 37.2% for HCF) while the impact of Hurricane Polo in October 2014 caused higher mortality in transplants started during the rainy season (up to 55%). We conclude that (i) coral transplantation on rock boulders is a good choice to restore damaged coral communities, (ii) BCF seems to be the best source of transplants for pocilloporid corals, and (iii) although high light availability during the rainy season enhances transplant growth, the stable, low energy conditions in the dry season facilitate initial transplant attachment and high survival.